Iran : a country study - Curtis, Glenn E. (Glenn Eldon), 1946-; Hooglund, Eric J. (Eric James), 1944- (Area handbook series., 2008)
From the Publisher: Offers a concise and objective examination of the dominant historical, geographic, social, economic, political, and military aspects of contemporary Iran. Contains five chapters on: Historical Setting, The Society and its Environment (covers geography, population, social systems, education, health, and welfare), The Economy (focuses on overview and sectorial analyses); Government and Politics (covers political institutions, political dynamics, and foreign policy); and National Security (covers military institutions and regional and national security problems/issues). Created by a multidisciplinary team of social scientists under the guidance of the Federal Research Division of the Library of Congress. This publication seeks to provide a basic understanding of Iranian society, striving for a dynamic rather than a static portrayal. Represents the analysis of the authors and should not be construed as an expression of an official U.S. government position, policy, or decision.